Influence of Project Based Learning Model Assisted by Interactive Digital Media on Students’ Critical Thinking Skill in Social Science and Science Subjects at Elementary School - Diana Isrianti; Yulina Ismiyanti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to examine the influence of the Project Based Learning learning model assisted by interactive digital media on the critical thinking skills in science and science subjects of fifth grade students at Al Fattah Islamic Elementary School. This research uses quantitative research methods with a Pre-Experimental Research Design type One Group Pretest-Posttest Design. The sample for this research was the fifth grade students of Al Fattah Islamic Elementary School, totaling 15 students. The data collection technique was carried out in the form of a description type test with 10 questions given during the pretest and post-test. Data analysis techniques include research instruments consisting of validity, reliability, distinguishing power and level of difficulty tests, then normality tests and paired sample t-test hypothesis tests to determine the comparison of pretest and post-test average scores. The research results show that the Project Based Learning learning model assisted by interactive digital media can improve students' critical thinking abilities. This is proven by the difference in the average score at the pretest of 44.07 and at the post-test of 86.33. In the results of the paired sample t-test, the sig value was obtained. (2-tailed), namely 0.000 < 0.05, then H0 is rejected and Ha is accepted. Thus, it can be concluded that the Project Based Learning learning model assisted by interactive digital media has an influence on the critical thinking skills of the science and science subjects of fifth grade students at Al Fattah Islamic Elementary School.